2013
DOI: 10.1002/eqe.2321
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic coupling dampers (VCDs) for enhanced wind and seismic performance of high‐rise buildings

Abstract: SUMMARY As high‐rise buildings are built taller and more slender, their dynamic behavior becomes an increasingly critical design consideration. Wind‐induced vibrations cause an increase in the lateral wind design loads, but more importantly, they can be perceived by building occupants, creating levels of discomfort ranging from minor annoyance to severe motion sickness. The current techniques to address wind vibration perception include stiffening the lateral load‐resisting system, adding mass to the building,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(36 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…The steel coupling beam with the central fuse had excellent energy‐dissipation capacity and exhibited a relatively low level of damage . Christopoulos et al developed a viscous coupling damper (VCD) with a replaceable shear‐critical structural fuse to accommodate the short span of the coupling beams. Nonlinear dynamic analysis indicated that fewer coupling beams were damaged or required repair due to the installation of VCDs, and analytical models of the VCDs as well as the tall shear walls with VCDs were proposed and verified .…”
Section: Introductionmentioning
confidence: 99%
“…The steel coupling beam with the central fuse had excellent energy‐dissipation capacity and exhibited a relatively low level of damage . Christopoulos et al developed a viscous coupling damper (VCD) with a replaceable shear‐critical structural fuse to accommodate the short span of the coupling beams. Nonlinear dynamic analysis indicated that fewer coupling beams were damaged or required repair due to the installation of VCDs, and analytical models of the VCDs as well as the tall shear walls with VCDs were proposed and verified .…”
Section: Introductionmentioning
confidence: 99%
“…The replaceable part and the elastic parts were connected by bolts, which could be replaced readily after being damaged. Montgomery et al developed a viscoelastic (VE) coupling damper, which consisted of layers of VE material sandwiched between layers of steel plates. Nonlinear dynamic analysis of tall buildings incorporating VE coupling dampers demonstrated good performance under winds and earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid passive control damper (HPCD) consisting of high-damping rubber damper in series with a buckling-restrained brace (BRB) was developed to dissipate multilevel seismic energy [12]. Christopoulos and Montgomery suggested that viscoelastic coupling damper (VCD) consists of VE material, steel plate, and anchor to reduce both the wind and earthquake response of tall shear wall buildings [13]. A hybrid damper which combines a friction damper and steel strip damper is proposed for improving the seismic performance of structures at multiple levels by Lee et al [14].…”
Section: Introductionmentioning
confidence: 99%